The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.12712/rpca.v15i2.48890
|View full text |Cite
|
Sign up to set email alerts
|

Falsos discursos mercadológicos

Abstract: O trabalho teve como objetivo compreender a reação dos consumidores às peças publicitárias que contêm apelos caracterizados como greenwashing versus bluewashing. A revisão da literatura focou na discussão acerca do marketing verde e societal, posteriormente discorrendo sobre esses falsos discursos mercadológicos. Como procedimento metodológico, foi realizado um experimento online em duas etapas, ambos com monitoramento ocular (eyetracker). O procedimento consistiu na apresentação de uma peça publicitária fictí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
1
0
2
Order By: Relevance
“…These results agree with some studies that also found such inconsistencies, with participants buying the green image, despite the fact they declare themselves as critics of that (Andreoli, Lima & Prearo;Andreoli & Nogueira, 2021). However, on the other hand, others question that they supported the capacity of participants to identify the greenwashing practice and mine occasional positive effects of it in their assessments (Markham, Khare & Beckman, 2014;Guo, Tao, Li & Wang, 2017).…”
Section: Results Discussionsupporting
confidence: 89%
“…These results agree with some studies that also found such inconsistencies, with participants buying the green image, despite the fact they declare themselves as critics of that (Andreoli, Lima & Prearo;Andreoli & Nogueira, 2021). However, on the other hand, others question that they supported the capacity of participants to identify the greenwashing practice and mine occasional positive effects of it in their assessments (Markham, Khare & Beckman, 2014;Guo, Tao, Li & Wang, 2017).…”
Section: Results Discussionsupporting
confidence: 89%
“…As participants agreed to the terms, the actual collection procedure began. There were three metrics of interest: emotional reaction to the ad, with eight assertions, a scale originally developed by Wells (1964) and recently adapted by Andreoli and Nogueira (2021); interest and willingness to purchase, a scale with four assertions, adapted according to the logic of the net promoter score (NPS); and the evaluation of communication responsibility, a scale developed for this study, with eight assertions. All these scales had a random presentation of the statements for each participant, who was asked to assign an agreement score on a Likert-type scale from 0 to 10, with 0 being totally disagree and 10 being totally agree.…”
Section: Methodological Proceduresmentioning
confidence: 99%
“…Sendo assim, o material utilizado consistiu na manipulação da exposição de um produto alimentício (fruta uva), que pode ser argumentado como tradicional quanto à caracterização de orgânico, comparando-se o selo oficial Orgânico Brasil e um selo fictício, desenvolvido apenas para este estudo. Para esse último, utilizou-se da denominação de natural, tendo em vista sua evidência como um dos principais indícios da prática de greenwashing, mais comumente chamado de "pecados de greenwashing" (Andreoli & Nogueira, 2021). Abaixo, na figura 1, expõe-se o material utilizado.…”
Section: Procedimentos Metodológicosunclassified
“…Aqui, foi seguida a orientação de Pradeep (2012, p.23), de limitação da amostra demandada quando da adoção de técnicas neurocientíficas, estimada em aproximadamente 10% das quantidades necessárias para as pesquisas tradicionais. Utilizou-se como referência de procedimento artigos concernentes, voltados à investigação do greenwashing (ver Andreoli & Batista, 2020;Andreoli & Nogueira, 2021).…”
Section: Etapa Exploratóriaunclassified